NO+ + H2: Potential energy surface and bound state calculations - Orek, Cahit; Uminski, Marcin; Klos, Jacek; Lique, Francois; Zuchowski, Piotr S.; Bulut, Niyazi (Elsevier, 2021)
The first four-dimensional (4D) adiabatic potential energy surface (PES) for the interaction of NO+ cation with the H-2 molecule has been accurately determined using the CCSD(T)-F12a method with cc-pVTZ-F12 basis set augmented with mid-bond functions. A detailed characterization of the PES and lowest bound states of the H-2-NO+ complex have been provided. The H-2-NO+ PES exhibits a single global minimum with a well depth of 824.63 cm(-1) corresponding to off-planar structure with the H-2 molecule in a perpendicular orientation to the NO+ cation. The solution of the nuclear Schrodinger equation for the bound states gives a zero-point energy corrected dissociation energy of D-0 = 498.15 cm(-1) for para-H-2-NO+ complex, and of 541.35 cm(-1) for ortho-H-2-NO+.
Keywords: Potential energy surface; Bound states calculations